RANCANG BANGUN WEBSITE E-COMMERCE PERJALANAN WISATA DI INDONESIA - Karolita, Devi; Ronaldo, Deddy; Centauri, Beta (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2015)
The need to entertain ourselves has increased ones need to travel, either inside or outside the country.This condition leads the travel agents increasingly promoting their tour packages. The website that isproposed in this reasearch attempts to provide the information of tour packages offered by several travelagents and the travel agents have a media to promote their tour packages widely. The travelers can alsoreview the travel destination on the website.The methodology used in the proposed website is UML-based Web Engineering (UWE). Thismethodology is consist of four (4) phases: Use Case Models, Models Content, Navigation Models andPresentation Models.The result using Blackbox Testing show that this website functionated as expected and can be used asa medium of information for travelers to book tour packages provide by registered travel agents.